A combination therapy of neural and glial restricted precursor cells and chronic quipazine treatment paired with passive cycling promotes quipazine-induced stepping in adult spinalized rats. (November 2015) - Dugan, Elizabeth A.; Shumsky, Jed S.
Abstract : Introduction: In order to develop optimal treatments to promote recovery from complete spinal cord injury (SCI), we examined the combination of: (1) a cellular graft of neural and glial restricted precursor (NRP/GRP) cells, (2) passive exercise, and (3) chronic quipazine treatment on behavioral outcomes and compared them with the individual treatment elements. NRP/GRP cells were transplanted at the time of spinalization. Methods: Daily passive exercise began 1 week after injury to give sufficient time for the animals to recover. Chronic quipazine administration began 2 weeks after spinalization to allow for sufficient receptor upregulation permitting the expression of its behavioral effects. Behavioral measures consisted of the Basso, Beattie, and Bresnahan (BBB) locomotor score and percent of weight-supported steps and hops on a treadmill. Results: Rats displayed an increased response to quipazine (BBB ≥ 9) beginning at 8 weeks post-injury in all the animals that received the combination therapy. This increase in BBB score was persistent through the end of the study (12 weeks post-injury). Conclusion: Unlike the individual treatment groups which never achieved weight support, the combination therapy animals were able to perform uncoordinated weight-supported stepping without a body weight support system while on a moving treadmill (6.5 m per minute) and were capable of supporting their own weight in stance during open field locomotion testing. No regeneration of descending serotonergic projections into and through the lesion cavity was observed. Furthermore, these results are a testament to the capacity of the lumbar spinal cord, when properly stimulated, to sustain functioning locomotor circuitry following complete SCI.